2009
DOI: 10.2166/wh.2009.035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental factors on the fecundity, hatchability and survival of snail Lymnaea (Radix) acuminata (Lamarck): vector of fascioliasis

Abstract: Lymnaea acuminata breeds round the year. The effect of pH, temperature, dissolved oxygen, carbon dioxide, light/dark period and clean/polluted water on the fecundity, hatchability and survival of young snails of L. acuminata were studied. It was observed that these environmental variant abiotic factors caused a significant variation in fecundity, hatchability and survival of young snails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The impeding of breeding of animals during winter period was not broken even by a 3-week acclimation at a temperature of 19°C and natural photoperiod, which is in accordance with the observations of other authors (Maat et al, 1982;Goldman, 2001). Jigyasu and Singh (2010) argued that the primary factor deciding the initiation of reproductive activity is not a temperature but the proper photoperiod. At the acclimation temperature snails fed few and moved little, which was a further difference with individuals tested in the May-September period ( _ Zbikowska and Cichy, 2011) and could affect their lowered thermal preference.…”
Section: Discussionsupporting
confidence: 90%
“…The impeding of breeding of animals during winter period was not broken even by a 3-week acclimation at a temperature of 19°C and natural photoperiod, which is in accordance with the observations of other authors (Maat et al, 1982;Goldman, 2001). Jigyasu and Singh (2010) argued that the primary factor deciding the initiation of reproductive activity is not a temperature but the proper photoperiod. At the acclimation temperature snails fed few and moved little, which was a further difference with individuals tested in the May-September period ( _ Zbikowska and Cichy, 2011) and could affect their lowered thermal preference.…”
Section: Discussionsupporting
confidence: 90%
“…42 Embryological development is highly influenced by the change of ecological factors in aquatic environment. 9 Ranjan 43 stated that breeding season and the incubation period vary with the nature of the environment. Raut 44 concluded that the rate of breeding in the number of snail's viz., Lymnaea acuminata, Indoplanorbis exustus and Acrostoma variabilis were governed by temperature, rainfall and food.…”
Section: Role Of Environmental Factorsmentioning
confidence: 99%
“…Abiotic factors increases the rate of reproductive capacity. 9 Srivastava et al 10 reported significant positive correlation between acetyl cholinesterase and egg laying in Lymnaea acuminata a fresh water pulmonates. The aim of the present review is demonstrate the role CDCs cells, their structure and mechanism involve in reproduction behavior of pulmonates.…”
Section: Introductionmentioning
confidence: 99%
“…It is regarded as a rapid and efficient method of reducing or eliminating transmission, as well as breaking up the parasite life cycle ( MELLO-SILVA et al . 2006 , JIGYASU & SING 2010 ). The search for local molluscicidal plants was considered more sustainable than the use of synthetic drugs (HAMMAMI et al .…”
Section: Introductionmentioning
confidence: 99%